Distributed Multi-Objective Metaheuristics for Real-World Structural Optimization Problems. (16th June 2016) - Luna, Francisco; Zavala, Gustavo R.; Nebro, Antonio J.; Durillo, Juan J.; Coello, Carlos A. Coello
Abstract : The design of bar structures in civil engineering is a complex problem when dealing with real-world structures. An approach to deal with these problems is to apply metaheuristics, which are stochastic methods based on iteratively producing and evaluating tentative solutions. In particular, we focus on multi-objective metaheuristics, as we consider two goals to be minimized: the weight and the deflection of the structure. When applying these techniques to real-world problems, running a metaheuristic for several thousands of evaluations may require many days on a single processor. In this paper, we develop distributed master/slave versions of four multi-objective metaheuristics that are representative of the state-of-the-art and apply them to optimize the design of two instances of a cable-strayed bridge. Our study reveals that our parallel proposals are able to effectively use up to 450 cores, providing accurate solutions in a short time.